Hubungan Kekerabatan Fenetik 6 Spesies Anggota Genus Hibiscus Berdasarkan Karakter Morfologi - Dian Palupi; Riska Desi Aryani; Sukarsa Sukarsa; Sri Lestari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The Hibiscus genus is a member of the Malvaceae family with striking flowers of various colors. Hibiscus is a genus that is easy to find in Indonesia because it is usually used as an ornamental plant, hedge plant, cut flower, medicinal plant, or tea for drinking. This research was conducted to know the phenetic relationship of 6 species of Hibiscus based on morphological characters. The research was conducted by observing 57 morphological characteristics of 6 species of Hibiscus, then UPGMA (Unweighted Pair Group Method with Arithmatic Mean) analysis using MEGA 11 software. The samples in this study were six species belonging to the Hibiscus genus, namely Hibiscus rosa-sinensis L., Hibiscus tiliaceus L., Hibiscus macrophyllus (Blume) Okenlada, Hibiscus mutabilis L., Hibiscus sabdariffa L., and Hibiscus acetosella Welw. ex Hiern. The results showed that 6 species of Hibiscus formed 3 clusters based on differences in habitus and stem diameter. H. tiliaceus and H. macrophyllus formed cluster one, H. acetosella and H. sabdariffa formed cluster two, while H. rosa-sinensis and H. mutabilis formed cluster three. The closest phenetic relationship is between H. acetosella and H. sabdariffa, with a dissimilarity index of 0.140 or 86% similarity. The furthest phenetic relationship was in H. rosa-sinensis and H. macrophyllus with a dissimilarity index of 0.737 or a similarity percentage of 26.3%.